Treatment of cutaneous leishmaniasis with thermotherapy in Brazil: an efficacy and safety study - Sheila Viana Castelo Branco Gonçalves; Carlos Henrique Nery Costa (Sociedade Brasileira de Dermatologia, 2018)
Abstract: BACKGROUND: Pentavalent antimonials remain as the standard drugs in the treatment of cutaneous leishmaniosis. The high cost, difficult administration, long treatment time, toxicity and increasing morbidity are factors that limit the use of these drugs. OBJECTIVES: To describe the response to radiofrequency thermotherapy in the treatment of localized cutaneous leishmaniasis in Brazil, and to evaluate its safety and tolerability. METHODS: We conducted a non-comparative open trial with a total of 15 patients confirmed to have cutaneous leishmaniasis on parasitological examination. A single radiofrequency thermotherapy session at 50ºC for 30 seconds was applied to the lesion and its edges. In patients with more than one lesion, only the largest one was treated initially. If after 30 days there was no evidence of healing, the smaller lesion was also treated with thermotherapy. Clinical cure was defined as visible healing for three months after treatment. The patients were followed-up for six months and there was no follow-up loss. RESULTS: Of all 23 lesions, only two evolved to complete healing without the need of treatment. Of 21 lesions, 18 (85.7%) achieved full healing. The main observed side effects were itching, burning sensation, pain and blisters. STUDY LIMITATIONS: Sample with a small number of patients and short follow-up. CONCLUSION: Thermotherapy can be considered a therapeutic alternative in localized cutaneous leishmaniasis, especially in cases of single cutaneous lesions and with formal contraindications to conventional treatment with pentavalent antimonials.